Dividend Policy Relevancy in Theoretical and Practical Economics - Gordon, David (International Journal of Business, Economics and Management, 2014)
The foremost purpose of this paper is to concisely explain to individuals teaching economics in an academic setting or using economics in a practical setting some of the basics of long run financial theory focusing on the dividend policy decision of a corporation. The main motivation for this study is based on observations of economists being very deficient in the discipline of finance especially in long run financial concepts. Many times practitioners or academics who are educated in the area of economics lack any type of background in finance and therefore are deficient with their knowledge of financial theory and applications. This disconnect prevents using many financial applications in their own classes, in their own businesses or with their own research. This paper serves as a primer to some of the long run dividend policy theories that individuals can use as a starting point to their additional research, study or use in teaching. Areas related to dividend policy and financial theory in general can be utilized by economists in academia and the private sector to enhance and advance their professional careers.